(untitled) (Journal of Business and Technology (Dhaka), 2016)
Liquidity risk may arise from diverse operations of financial intermediaries, facilitators and supporters as they are fully liable to make available liquidity when required by the third party. Incase of Islamic Banks additional efforts are required for scaling liquidity management due to their unique characteristics and conformity with Shariah principles. The objective of this study is to look into the liquidity risk associated with the solvency of the financial institutions, with a purpose to evaluate liquidity risk management (LRM) through a comparative analysis between conventional and Islamic banks of Bangladesh. This paper investigates the significance of Size of the Firm, Net Working Capital, Return on Equity, Capital Adequacy and Return on Assets (ROA), on Liquidity Risk Management in conventional and Islamic banks in Bangladesh. The study has taken six mid-size banks- three conventional and three Islamic banks as samples. It is based on secondary data which are collected from the selected banks annual reports, covering a period of 2007-2011. Independent variables that have positive but insignificant relation are; size of the bank and net working capital to liquidity risk in Islamic banks and in case of conventional banks size of bank is negatively related with the liquidity risk. Only return on assets is positively affecting the liquidity risk at 10% level in case of conventional banks, but in Islamic banks the relationship is insignificant. The other variables are found to be insignificant in affecting the liquidity risk for both the conventional and Islamic banks in Bangladesh Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 18-35